The effect of topical atropine 0.05% compared to atropine 0.01% for Myopia control in Children : A Meta-analysis: Poster Presentation - Observational Study - General practitioner - DEWI, INGGRIANA SUKMA; SAVITA, SALMA (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Myopia is the most common ocular anomaly manifesting during primary school and progresses until a mean age of 16, but rarely beyond age of 25. Atropine, a nonselective muscarinic antagonist, has been studied widely in recent years as an option for myopia control. To analyse the efficacy of Atropine 0,05% compared with Atropine 0,01 % for myopia control in children aged 4-16 years toward the axial length examination through a meta-analysis. Methods : A systematic search was performed using Medline and Cochrane database up to December 2022. Review was performed according to the PRISMA Statement. The eligible studies were RCTs which comparing Atropine concentration 0.05% with 0.01%. Results : From 101 retrieved articles, 5 trials involving total 1035 patients were included. The follow-up period of the studies was 1-2 year. The analysis shows Atropine 0,05% significantly decrease axial length (Mean Difference [MD]: -0.11, 95%CI [-0.15-0.07], p<0.00001, I2= 99 %) comparing to Atropine 0,01%. Conclusion : In myopia control in children, atropine 0,05 % was more effective to reduce myopia progression in controlling axial length elongation over a period of 1-2 year comparing to atropine 0,01%.